Song Is Not the Same Jews and American Popular Music (Purdue University Press, 2011)
This volume of the Casden Institute's The Jewish Role in American Life annual series introduces new scholarship on the long-standing relationship between Jewish-Americans and the worlds of American popular music. Edited by scholar and critic Josh Kun, the essays in the volume blend single-artist investigations with looks at the industry of music making as a whole. They range from Jewish sheet music to the risqué musical comedy of Belle Barth and Pearl Williams, from the role of music in the shaping of Henry Ford's anti-Semitism to Bob Dylan's Jewishness, from the hybridity of the contemporary "Radical Jewish Culture" scene to the Yiddish experiments of 1930s African-American artists. Contents: Foreword (Gayle Wald); Introduction (Josh Kun); "Cohen Owes Me Ninety-Seven Dollars, and other Tales from the Jewish Sheet- Music Trade" (Jody Rosen); "'Dances Partake of the Racial Characteristics of the People Who Dance Them' : Nordicism, Antisemitism, and Henry Ford's Old Time Music and Dance Revival" (Peter La Chapelle); "Ovoutie Slanguage is Absolutely Kosher: Yiddish in Scat- Singing, Jazz Jargon, and Black Music" (Jonathan Z. S. Pollack); "'If I Embarrass You, Tell Your Friends' : Belle Barth, Pearl Williams, and the Space of the Risque" (Josh Kun); "'Here's a foreign song I learned in Utah' : The Anxiety of Jewish Influence in the Music of Bob Dylan" (David Kaufman); "Jazz Liturgy, Yiddishe Blues, Cantorial Death Metal, and Free Klez: Musical Hybridity in Radical Jewish Culture" (Jeff Janeczco).